MARKETING STRATEGY FOR OIL PALM NURSERY WITH A SWOT ANALYSIS APPROACH AT PT. UTAMA KARYA TANI - Reva Revanza; Hamzah Manurung; Tifany Zia Aznur (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
This study aims to identify strengths and weaknesses in oil palm seed marketing, analyze opportunities and threats that influence marketing, and formulate an effective marketing strategy based on a SWOT analysis at PT. Utama Karya Tani. The study was conducted at PT. Utama Karya Tani during March–May using descriptive methods with a qualitative approach. Data were obtained through observation, interviews, and documentation, then analyzed using descriptive analysis and SWOT analysis through the preparation of the Internal Factor Analysis Summary (IFAS), External Factor Analysis Summary (EFAS), and SWOT Matrix. The results show that the company's main strengths include good seed quality, the use of certified seeds, good relationships with customers, and business experience. Meanwhile, the company's weaknesses include limited promotion, suboptimal digital marketing, a limited distribution network, and price competition. From the external side, the main opportunities come from the increasing demand for oil palm seeds, the People's Oil Palm Replanting Program (PSR), developments in information technology, and increasing farmer awareness of the use of superior seeds. Threats faced by the company include competition in the nursery business, fluctuating economic conditions, increasing production costs, and changes in market conditions. The analysis results show an IFAS value of 0.78 and an EFAS value of 0.65, placing PT Utama Karya Tani in Quadrant I (Strength–Opportunity). This position indicates that the company is in a favorable position, so the recommended strategy is an aggressive strategy (SO), which utilizes the company's strengths to seize opportunities through improving product quality, setting competitive prices, expanding distribution networks, and optimizing digital-based promotions.